Association between itching and the serum zinc levels in patients with varicose veins - Yasushi Takai; Keiichi Hiramoto; Yoshiyuki Nishimura; Ryota Uchida; Keigo Nishida; Kazuya Ooi (BMC, 2017)
Abstract Background Varicose veins commonly occur in the lower extremities and can cause pain and discomfort in the affected area. Many patients with varicose veins suffer from itching, but its cause has not been sufficiently explained. In recent years, the role of zinc in maintaining the integrity of skin has been reported, and zinc supplementation has been suggested to be effective in relieving itching. The objective of this study is to elucidate the relationship between itching and serum zinc concentration in patients with varicose veins. Methods We measured the stratum corneum water content, TEWL and zinc levels in each participant. The study subjects were 11 patients with varicose veins who were experiencing itching (2 males and 9 females, mean age: 65.9 ± 9.4 years old) and 13 patients without itching (6 males and 7 females, mean age: 59.3 ± 9.5 years old). The control group was comprised of 9 healthy individuals without varicose veins (mean age: 41.7 ± 7.0 years old). Results The level of stratum corneum water content was significantly lower in the patients experiencing itching compared to those without the symptom, and it was significantly lower in both patient groups than in the control group. Transepidermal water loss (TEWL) was significantly higher in the patients experiencing itching than those without the symptom, and it was significantly higher in both patient groups than in the control group. In addition, zinc level was significantly lower in the patients with itching compared to those without itching or the control group. For all study participants, relationships between the stratum corneum water content and TEWL against serum zinc were examined. There was a positive correlation between the stratum corneum water content and serum zinc, and a negative correlation was found between TEWL and serum zinc. Conclusion Our novel findings suggested that the development of varicose veins leads to decrease in serum zinc, causing dry skin which could contribute to itching.